2002
DOI: 10.1074/jbc.m107731200
|View full text |Cite
|
Sign up to set email alerts
|

Coaggregation, Cointernalization, and Codesensitization of Adenosine A2A Receptors and Dopamine D2Receptors

Abstract: Adenosine and dopamine signaling exert opposite effects in the basal ganglia, a brain region involved in sensory-motor integration. Thus, adenosine agonists induce motor depression and adenosine antagonists, such as caffeine, produce motor activation (1). These opposite effects result from specific antagonistic interactions between subtypes of adenosine and dopamine receptors in the striatum, the main input structure of the basal ganglia. In fact, striatal dopamine receptors and, to some extent, adenosine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
341
1
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 462 publications
(361 citation statements)
references
References 35 publications
14
341
1
5
Order By: Relevance
“…Stimulation of A 2A receptors decreases the affinity of D 2 receptors for agonists by means of an intramembrane interaction (Ferré et al, 1991), while stimulation of D 2 receptors inhibits A 2A receptor-induced activation of adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002). By means of the strong antagonistic D 2 -A 2A receptor interaction at the adenylyl cyclase level, and due to the existence of a tonic effect of dopamine on D 2 receptors, under normal conditions A 2A receptors are practically unable to activate the cAMP-PKA signaling pathway (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of A 2A receptors decreases the affinity of D 2 receptors for agonists by means of an intramembrane interaction (Ferré et al, 1991), while stimulation of D 2 receptors inhibits A 2A receptor-induced activation of adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002). By means of the strong antagonistic D 2 -A 2A receptor interaction at the adenylyl cyclase level, and due to the existence of a tonic effect of dopamine on D 2 receptors, under normal conditions A 2A receptors are practically unable to activate the cAMP-PKA signaling pathway (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…A 2A and D 2 receptors exert reciprocal antagonistic interactions that modulate the function of GABAergic enkephalinergic neurons (Ferré et al, 1993(Ferré et al, , 1997Agnati et al, 2003) and recent studies have demonstrated the ability of A 2A and D 2 receptors to heteromerize Kamiya et al, 2003;Ciruela et al, 2004;Woods and Ferré, 2005). A 2A and D 2 receptors are prototypical G s -and G i -coupled receptors, respectively, which play opposite effects on adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002;Lee et al, 2002). Stimulation of A 2A receptors can potentially stimulate striatal adenylyl-cyclase, with the consequent activation of the cAMP-PKA signaling pathway and the induction of the expression of different genes, such as c-fos and preproenkephalin (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…These results also demonstrate for the first time that a chronic A 2A blockade, via the administration of its selective antagonist CSC, is effective against the 6-OHDA-induced akinetic deficits. In view of the recent demonstration that A 2A and mGlu 5 receptors can form heteromeric complexes (Ferré et al, 2002) as well as coaggregate and cointernalize with the DA D 2 receptors after their prolonged stimulation (Hillion et al, 2002), the idea of a reciprocal adaptation of these receptors subtypes appear to be further corroborated. It seems therefore conceivable that intramembrane interactions implying common final pathways between striatal A 2A and mGlu 5 receptors could have been involved in the functional synergism underlying the efficient recovery of the akinesia observed in the present study.…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 98%
“…Animals were maintained in accordance with guidelines of the Institutional Care and Use Committee of the Intramural Research Program, National Institute on Drug Abuse, NIH. Rats were (Hillion et al, 2001) and anti-CB 1 receptor rabbit polyclonal IgG (PA1-745; Affinity BioReagents, Golden, CO, USA). The selectivity of both antibodies has been previously characterized (Hillion et al, 2001;Twitchell et al, 1997 Immunocytochemistry SH-SY5Y cells were grown on glass coverslips coated with poly-L-lysine (Sigma).…”
Section: Co-immunoprecipitationmentioning
confidence: 99%
“…Rats were (Hillion et al, 2001) and anti-CB 1 receptor rabbit polyclonal IgG (PA1-745; Affinity BioReagents, Golden, CO, USA). The selectivity of both antibodies has been previously characterized (Hillion et al, 2001;Twitchell et al, 1997 Immunocytochemistry SH-SY5Y cells were grown on glass coverslips coated with poly-L-lysine (Sigma). At 60% confluence, cells were rinsed with PBS, fixed in 4% paraformaldehyde for 15 min, and washed with PBS containing 20 mM glycine.…”
Section: Co-immunoprecipitationmentioning
confidence: 99%